The influence of stress on the oxidation of a Ni-based superalloy. (1st July 2019) - Ramsay, J.D.; Evans, H.E.; Child, D.J.; Taylor, M.P.; Hardy, M.C.
Highlights: External chromia thickness was unaffected by stress. Tensile stress resulted in increase of alumina penetration by factor of 2. This is taken to be evidence of Stress Aided Grain Boundary Oxidation (SAGBO). Tensile stress at the tip of the intrusion increases the anion vacancy concentration. Leads to flux of oxygen vacancies along intrusion, increasing the growth rate. Abstract: Double edge notched specimens of the Ni-based superalloy RR1000 have been subjected to 1-1-1-1 fatigue tests with R = 0 at 750 °C in air for 111 h at a peak elastic stress of 900 MPa. Extensive measurements of the thickness of the chromia layer formed during this exposure period show no influence of the applied stress. In contrast, the depth of the intergranular alumina penetrations underlying the chromia layer were approximately a factor of 2 larger in the most stressed regions (base of the notches) than in unstressed regions adjacent to the notches. This difference was highly significant and is considered to demonstrate Stress Aided Grain Boundary Oxidation (SAGBO). A model for this process has been developed in which the tensile stress at the tip of the alumina intrusion increased the anion vacancy concentration there and the vacancy flux along the intrusion. A consequence was that the intrusion growth rate increased above that in the absence of stress. The observed increase of a factor of 2 in intrusion length is estimated to be achievable at a tensile stress of ˜1 GPa within the intrusion at its tip. This is considered to be plausible in such a high-strength alloy.